To study and analyze the design of drive shafts for automobiles using composite material through empirical review on literature. (2022) - Ahsan Feroz, Ahmad; Harshit,; Chawla, Dinesh; Kumar, Rajender
Abstract: An Automobile drive shaft is the important component of a vehicle. The high-quality steel is mainly used as the material for the drive shafts. Still, there are some challenges such as damping, stiffness that limits the usage of high-quality steels for drive shafts manufacturing. To overcome such challenges, the usage of composite materials is now been increased rapidly. The composite material has the potentials to provide the required stiffness and damping. Even the weight to strength ratio is better in composite materials in comparison to steels. The present study is based on extensive literature review to provide insights on composite materials used for drive shaft manufacturing.